The birth of a (fake?) nation at the aftermath of the decomposition of USSR. The unsolved issue of post-Soviet 'frozen conflicts' - Marsili, M. (Proelium, 2016)
This paper analyzes the situation of some states (Abkhazia, Nagorno Karabakh, South Ossetia and Transnistria), de facto independent after the dissolution of the USSR, which have been being in a limbo for 25 years, hovering between being considered 'fake states' and from getting the international legal status to which aspire. There is the problem of identifying the objective requirements for their largely recognition, which otherwise remains merely a discretionary choice of the other actors in the international society, based on purely political requirements and economic interests. In a world made up of states, which are the main actors on the international stage, how can these entities get the 'certification' of de jure sovereign states?